2022
DOI: 10.3390/ma15196993
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Performance of Segmental CFST Piers with External Energy Dissipators under Lateral Cyclic Loadings

Abstract: In order to improve the construction efficiency of piers and reduce the local damage of piers, concrete-filled steel tubes (CFST) are used to precast pier segments. Aiming at the problems of the poor integrity and insufficient energy dissipation capacity of dry joint segmental assembled piers, segmental assembled concrete-filled steel tubular piers with external replaceable energy dissipators are being developed. Based on the low cyclic test of a segmental assembled CFST pier, the finite element numerical simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Using ANSYS to analyze the damper, it was found that, compared with slot type and double X-shaped mild steel dampers, the rhombic hole damper had the largest shear stiffness, and the major axis of the rhombic hole and the thickness of the steel plate of the damper had the largest impact on the damping force of the damper; however, the thickness of the steel plate had little effect on the maximum stress of the damper [ 19 ]. In 2022, Wang et al [ 20 ] designed a rhombic opening connection device for the pier joint and used ABAQUS finite element software to conduct a quasi-static analysis of the device. The results showed that improving the section ratio can improve the lateral bearing capacity and energy dissipation capacity of the pier.…”
Section: Introductionmentioning
confidence: 99%
“…Using ANSYS to analyze the damper, it was found that, compared with slot type and double X-shaped mild steel dampers, the rhombic hole damper had the largest shear stiffness, and the major axis of the rhombic hole and the thickness of the steel plate of the damper had the largest impact on the damping force of the damper; however, the thickness of the steel plate had little effect on the maximum stress of the damper [ 19 ]. In 2022, Wang et al [ 20 ] designed a rhombic opening connection device for the pier joint and used ABAQUS finite element software to conduct a quasi-static analysis of the device. The results showed that improving the section ratio can improve the lateral bearing capacity and energy dissipation capacity of the pier.…”
Section: Introductionmentioning
confidence: 99%